PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XII MIPA - Putri, Auliya (Departemen Matematika, 2023)
One thing that helps educators understand students’ abilities in learning mathematics is mathematical communication. However, math communication abilities are lacking among class XII MIPA SMAN 6 Padang students. This study explores how students' mathematical communication abilities are impacted by and developed by the Think-Pair-Share (TPS) cooperative learning approach. With a Randomised Control Group Only Design, a quasi-experimental methodology was used in this investigation. By gathering samples using standard random sampling techniques, 177 students from class XII at SMAN 6 Padang as the research population. Instruments included maths tests and quizzes. The data analysis gave the t-test a =0.000. P-Value 0.05 or lower rejects H0. Thus, cooperative learning of the TPS kind enhances students' mathematical communication abilities.Keywords– Mathematical Communication Ability, Cooperative Learning, Think-Pair-Share (TPS)